BOARD POWERS AND UNETHICAL ACCOUNTING OF PUBLIC QUOTED CORPORATIONS IN NIGERIA - Usman Abbas; Shehu Usman Hassan (Gusau Journal of Accounting and Finance, 2022)
Numerous scandals have been committed globally due to excessive use of unethical accounting. Various research has been conducted on board activities and unethical accounting and their discoveries were assorted. None to the researchers’ awareness examined such association in an entire population of the registered public non-financial corporations in Nigeria for a period of 10 years (2010-2019). Secondary data was extracted from the annual reports and accounts, companies’, and directors’ profile of the firms. The data was analyzed using Ordinary Least Square regression. The study found among other things that board power and its proxies except board capability have significant impact on the unethical accounting of listed firms in Nigeria. It is therefore, recommended that, the quoted firms in Nigeria should ensure the composition of allencompassing and robust audit committees. They should also guarantee the presence of assorted gender, varied ethnic groups, directors with national honor and oversea directors on the boards. The organizations should ensure the formation of risk management committee in the entire corporations. The management should guarantee the existence of vastly skilled, experienced, and knowledgeable directors on the boards as these will aid in curbing the unethical accounting. The implication of the outcomes of this research to literature is that the discoveries of the research are to be utilized by researchers in confirming tokenism/critical mass theory, social capital theory. Also, to validate upper echelon theory, efficient contracting theory, resource dependency theory, signaling theory, human capital theory, behavioral theory of corporate boards and governance and agency theory. The discovery of the study is only applicable to listed organizations in Nigeria. The research utilized only six proxies of board power which is a limiting factor, and the result of the study might vary if other substitutions of board power are utilized. Moreover, the research did not capture the financial sector of Nigerian economy for the reason that the unethical accounting model utilized of Collins et al (2017) has elements which are only relevant to non-financial corporations. If other models of unethical accounting that can capture the financial industry are applied, the outcome of research may had been changed.